Juventude rural e extensão: projetos institucionais e perspectivas juvenis - Masson, Ivanda (2013)
The aim of the thesis is to understand the processes of social construction of youth within the framework of non-formal education projects, deployed by rural extension and by other organizations in the Midwest of Santa Catarina, in southern Brazil. The study is part of the design that considers the rural youth a socially constructed category and specificities in different times, contexts, realities and possibilities. The methodological procedures combined documentary research and semi-structured interviews with representatives of rural institutions and young graduates of the 4-S Clubs and the pilot project "Entrepreneurship of Rural Youth", implemented by Rural Extension. While in the post-war context the rural extension agencies organized the rural youth into 4-S Clubs as a way to prepare them technically and ideologically for the modernization of agriculture, in the last decade both public and private institutions as well as non-governmental organizations have been active with the purpose of building a stand-alone rural youth, enterprising and committed to sustainable development. The rural youth, in turn, claim an effective participation in the processes of building alternatives for social inclusion aiming to break both the institutional and the familiar custody. It is concluded that the latest experiences of rural extension represent methodological advances regarding proposals historically directed to rural youth. However, the rural youth express the need for institutionalization of programs which contribute not only to the agricultural production They are perceptive and critical of the traditional way of speech and thinking the youth only as "future".